Rheological and chemical indices to characterize long-term oxidative aging of SBS/rubber composite-modified asphalt binders - Chen, Suhua; Zhuo, Shangzhi; Xu, Gang; Chen, Xianhua; Yu, Lin; Xu, Qi (Frontiers in Materials, 2024)
Oxidative aging of asphalt binders seriously affects the durability of asphalt pavements and causes early damage. Hence, the appropriate indices could track asphalt binders aging extent are of great importance to the material selection, design, and maintenance of asphalt pavement. This paper aims to select the applicable rheological and chemical indices to characterize oxidative aging degrees of polymer-modified asphalt binders. Styrene-butadiene-styrene (SBS) modified asphalt and two kinds of SBS/crumb rubber compound modified asphalt were subjected to Rolling Thin Film Oven (RTFO) test and 20, 40, 60 hours Pressure Aging Vessel (PAV) test. Various rheological experiments at a different temperature range were applied to obtain rheological indices including complex shear modulus (|G*|), G-R parameter, and J' (derivative of creep compliance). A range of chemical indices was determined by the Fourier Transform Infrared Spectroscopy (FTIR) test. The results indicate that the carbonyl index is strongly correlated with PAV aging time. |G*| at 52°C and J' values at -18°C are the two most promising rheological indices to track asphalt binder's oxidative aging and well relate to the chemical changes induced by PAV aging. Besides, G-R parameter is problematic in some instances when used as the rheological index because its values accuracy depends on the fitting precision of master curves.